Snakes of an urban-rural landscape in the central Andes of Colombia: species composition, distribution, and natural history - Rojas-Morales, Julián Andrés (Phyllomedusa: Journal of Herpetology, 2012)
From 2005 to 2011, I studied thecomposition, distribution and natural history of an Andean urban-rural snake assemblageat the Cordillera Central of Colombia, based on three data sources: (1) examination ofspecimens in the MHN-UC [Museo de Historia Natural, Universidad de Caldas], (2)incidental encounters by author, and (3) collection of data by other researchers. Additionally,I provide natural history notes for the species involved. A total of 14 species, includingtwo subspecies of snakes, belonging to 12 genera and four families, have been found in thestudied area (municipality of Manizales, Caldas). Taking into account this total, 10 had atleast one record in the urban area, 13 in the rural area and 14 in forested areas. OnlyLiophis epinephelus bimaculatus was found exclusively in forest environment. Threespecies (21.4%) are apparently endemic to the region, six species (42.8%) correspond to afauna representative of the Tropical–Andean range of South America, four species (28.5%)are distributed from Central America to the tropical Andes, and only one species is widelydistributed in the whole continent. The snake assemblage in Manizales is mostly terrestrial,and in general, the species tend to be more active in the rainy periods of the year (mainlyfrom October–December), and most of them may occasionally be found in urban areas,mainly close to areas of vegetation such as crops and pastures.